2021
DOI: 10.1155/2021/9299001
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Continuous Catheterization on Reducing Postoperative Urinary Tract Infection in Cervical Cancer Patients with Double J Stent Placement

Abstract: This study aims at exploring the effect of continuous catheterization on reducing postoperative urinary tract infection in cervical cancer patients with double J tube placement. To be specific, a retrospective analysis was performed on 120 cases of cervical cancer patients who underwent laparoscopic or open radical hysterectomy in Shengjing Hospital of China Medical University from January to December 2019. They were divided into a persistent group (n = 70) and a short-term group (n = 50) according to indwelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, the optimal duration of stent retention to reduce postoperative urinary complications remains a topic of debate. Research indicates that ureteral stents may not reduce the frequency of ureteral stricture in cervical cancer patients following radiotherapy [ 16 , 17 ]. Regular stent replacement and potential complications associated with stent placement make preoperative stent placement a cautious approach in the clinical management of cervical cancer patients receiving postoperative radiotherapy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal duration of stent retention to reduce postoperative urinary complications remains a topic of debate. Research indicates that ureteral stents may not reduce the frequency of ureteral stricture in cervical cancer patients following radiotherapy [ 16 , 17 ]. Regular stent replacement and potential complications associated with stent placement make preoperative stent placement a cautious approach in the clinical management of cervical cancer patients receiving postoperative radiotherapy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%